QUALITY PACKAGING AND SAFFRON EXPORT (Singaporean Journal of Business Economics and Management, 2013)
With the increasing development in different industries in country, the role of packaging is very important. Appropriate product packaging encourages consumers to buy products and if this packaging design and select by complete wisdom of manufacturers and exporters will distinguish company from other companies. Saffron is one of the traditional products of Iran and due to its high price in non-oil exports of the country, comparative advantage and its importance in terms of production; acreage and employment in different parts of the country allocated a particular position. Now basic problems in the export of Iranian saffron is down packaging that often is exported in form of bulk to neighboring countries such as emirates and it's packed in there and with more reasonable price is exported to final market.